Study of Transition Metal-Ligand Stability Constant with Some Substituted Pyrazolines-pH Metrically - N. Deshmukh, Prajakta; Jamode, V.S. (Asian Journal of Chemistry, 2010)
Complex formation between Cu(II), Co(II) and Ni(II) metal ions with 1-thiocarboxamido-3-(2- hydroxy-5-chlorophenyl)-4-bromo-5-(4-methoxy phenyl)pyrazoline (L1), 1-thiocarboxamido- 3-(2-hydroxy-5-chloro-phenyl)-4-bromo-5-phenyl pyrazoline (L2) and 1-thiocarboxamido-3-(2- hydroxy-3-bromo-5-chlorophenyl)-4-bromo-5-phenyl pyrazoline (L3) have been investigated by employing Bjerrum-Calvin pH metric techniques at 27 ºC in 70 % dioxane-water medium. The data obtained can be used for the determination of proton-ligand formation numbers (ηA). From the formation curve, proton-ligand stability constant pK values have been evaluated using half integral method. The metal-ligand formation numbers (η) are estimated by using Irving- Rossotti's expression. Metal-ligand stability constants for 1:1 and 1:2 complexes have been calculated which are designated by letters log K1 and log K2, respectively.